The Develompment of E-Worksheet to Tain Scientific Literacy on Membrane Transport Material for 11TH-Grade High School Students - Crystal Prima Yudha; Yuliani Yuliani (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2023)
Abstract Scientific literacy is the ability of a person to apply his knowledge to identify questions, construct new knowledge, provide scientific explanations, and develop a reflective mindset so that he can participate in overcoming science-related issues and ideas. Biological material that has the learning potential to train science literacy is membrane transport. The objective of this study is to create a membrane transport Eworksheet that is reliable, useful, and efficient for teaching scientific literacy and enhancing classroom instruction. A 4-D model research design was used to create the e-worksheet (Define, Design, Develop, Disseminate) without the Disseminate stage. A total of 30 students from class XI of science 3 took part in the trial. The parameter of this study is the validity of expert validation results, the applicability of student replies, and the efficacy of learning outcomes and scientific literacy abilities. The results showed that the validity of the developed E-worksheet received a percentage score of 97% and was included in the very decent category. The practicality of E-worksheet based on student responses obtained results of 96.65% included in the very practical category. The effectiveness reviewed based on the completeness of learning outcomes obtained results of 100% included in the very effective category and the achievement of science literacy indicators of 88.64%. These findings allow for the declaration that the E-worksheet is valid, practical, and effective.Keywords: E-worksheet, scientific literacy, membrane transport.